Comparative study of DTM height accuracy between LiDAR and aerial photograph - Noraizee Idris, 1986-; Khairul Anuar Abdullah, supervisor; Fakulti Geoinformasi dan Harta Tanah (2009)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2009